Algorithm of isolating the pauses in a speech signal (Damascus University Journal for engineering sciences, 2021)
The article considers an algorithm of isolating the active segments and  pauses in a speech signal. The developed algorithm is based on the use of the theory of active perception adapted for the analysis of speech signals and on speech signal segmentation.Results of the experiments confirm the capability of the offered algorithm a for solving the specific problem in speech processing area person  identification through (Speech Recognition System).
Keywords: digital signal processing; theory of active perception; speech signal analysis; speech signal segmentation; active segments; pauses isolation in a speech signal